Variability of preference toward mechanical ventilator settings: A model-based behavioral analysis - Allerød, Charlotte; Karbing, Dan S.; Thorgaard, Per; Andreassen, Steen; Kjærgaard, Søren; Rees, Stephen E. (Journal of critical care, 2011)
The purpose of this study was to evaluate Danish clinicians' opinions toward ventilator settings using standardized model-simulated patients. The models ensured that all clinicians received identical presentations of data and anticipated responses to changes in patient state, enabling opinions on the same patient cases to be obtained from different clinicians. Ten Danish intensive care clinicians' and a computerized decision support system each provided suggestions for respiratory frequency (f), tidal volume (Vt) and insoired oxygen fraction (FiO2) in the same 10 model-simulated patient cases. The 110 suggestions were then evaluated by the 10 clinicians in a ranking and classification procedure. Clinicians' preferences toward ventilator settings (Fi o 2, Vt, and f) and the resulting simulated values of arterial oxygen saturation, peak inspiratory pressure, and pH were significantly different ( P < .005). The results of the classification showed that clinicians generally had poor opinion of the advice provided by other clinicians and the decision support system, considering this advice to be unacceptable in 33% of cases and good only in 21%. The ranking procedure also showed that clinicians did not agree on the best and worst advice. The present study shows significant difference in opinion on appropriate settings of f, Vt, and Fi o 2 in the same computerized decision support system model–simulated patient cases.